ChemInform Abstract: Synthesis of 3‐Benzazepines and Azepino[4, 5‐b]heterocyclic Ring Systems via Intramolecular Friedel—Crafts Cyclization. Issue 29 (1st July 2013) - Kargbo, Robert B; Sajjadi‐Hashemi, Zohreh; Roy, Sujata; Jin, Xiaomin; Herr, R. Jason
Abstract: Allylic bromides tethered to activated aromatic rings undergo intramolecular Friedel—Crafts reaction in the presence of catalytic or equimolar amounts of Bi(OTf)3 .